EVALUATION OF UNDERGROUND DRINKING WATER QUALITY IN CENOMANIAN-LOWER CRETACEOUS AGUIFER COMPLEX IN KHARKIV REGION - Прибилова, В. М. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2016)
The article examined the problem of providing the population of Ukraine with quality underground drinking water. We give general projected groundwater resource in Ukraine. Average supply of forecast resources and production reserves of groundwater per capita has been examined and the place of Kharkiv region among the regions of Ukraine has been shown. The specified area of Kharkiv region has the highest rates of forecast resources. We present the main groundwater aquifers used for water supply within centralized Kharkiv region. The article analyzes the qualitative composition of underground drinking water in the aquifer of Cenomanian-Lower Cretaceous sediments in the water intakes of Kharkiv region.A comparative analysis was made as to the values of the chemical composition indicators of the groundwater aquifer complex Cenomanian-Lower Cretaceous deposits in the period of production intakes with regulations GosSanPiN 383-97 "Drinking Water". Dunn’s assessment of macro and micro component in groundwater is under existing water intakes. The chemical composition of underground drinking water within the main fields of Kharkiv region with confirmed reserves of underground water intakes are exploited on groundwater aquifer Cenomanian-Lower Cretaceous sediments. The conclusion regarding the prospects of using underground drinking water is to supply the population with this water that is more qualitative and protected from pollution than surface waters. Today the use of groundwater of Kharkiv region is only 4% of total resources.